2017
DOI: 10.1089/pop.2015.0179
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity Associated with Self-Efficacy and Acculturation

Abstract: Food insecurity is a significant public health issue that affects the physical and mental health of people of all ages. Higher levels of self-efficacy may reduce levels of food insecurity. In addition, acculturation is potentially an important factor for food insecurity among immigrant populations. The purpose of this study is to examine food insecurity associated with self-efficacy and acculturation among low-income primary care patients in the United States. A self-administered survey was administered in May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Different studies have described the association of socioeconomic characteristics with the psycho-social factors observed in our study. A large body of literature has examined the negative impact of socioeconomic deprivation on self-efficacy [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have described the association of socioeconomic characteristics with the psycho-social factors observed in our study. A large body of literature has examined the negative impact of socioeconomic deprivation on self-efficacy [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies assessing relationships between socioeconomic characteristics and psycho-social factors related to obesity have yielded inconsistent results. High levels of certain advantageous psycho-social factors like self-efficacy are less frequently present among individuals with low socioeconomic status [13][14][15], while others like body satisfaction are less frequently present among individuals with high socioeconomic status [16]. Since psycho-social factors are usually correlated, some authors have suggested that it is inappropriate to study obesity-related psycho-social factors independently from each other, and that a tool (e.g., an overall profile) combining various such factors should be developed to assess the overall impact of this family of mechanisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…High self-efficacy has been shown in adult populations to increase diet quality [26]. The limited existing literature also suggests an association between FI and self-efficacy [27]. Self-efficacy seems to be impaired by FI [28] and improvements in food security (FS)—regular and reliable access to sufficient nutritious food [29]—have been shown to increase self-efficacy [30].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were categorized to the following three groups: US born English speakers, non‐US born English speakers, and Spanish speakers. The reasoning for this is because previous studies have suggested that free clinic patients in these groups differ from each other in regards to health‐related behaviors . Participants who took the survey in English were considered English speakers, while those who took the survey in Spanish were considered Spanish speakers.…”
Section: Methodsmentioning
confidence: 99%